Interdecadal Modulation of the Pacific Decadal Oscillation on the Relationship Between Spring Arctic Oscillation and the Following Winter ENSO - Chen, Shangfeng; Chen, Wen; Ying, Jun; Zheng, Yuqiong; Lan, Xiaoqing (Frontiers in Earth Science, 2022)
Previous studies indicated that Arctic Oscillation (AO) in boreal spring is an important extratropical trigger for the outbreak of El Niño and Southern Oscillation (ENSO) events in the succedent winter. This study reveals that the Pacific Decadal Oscillation (PDO) has a strong modulation on the linkage between the spring AO and the following winter ENSO. Particularly, impact of the spring AO on the succedent winter ENSO is strong during positive PDO phase (+PDO). By contrast, the spring AO-winter ENSO connection is weak during negative PDO phase (−PDO). During +PDO, positive spring AO induces a marked anomalous cyclone over the subtropical North Pacific via wave-mean flow interaction. The subtropical cyclonic anomaly leads to sea surface temperature (SST) warming and enhanced atmospheric heating there, which could further propagate southward to the tropical central Pacific via wind-evaporation-SST feedback mechanism and thus impact following winter El Niño via tropical process. During −PDO, the spring AO-generated SST, and atmospheric circulation and heating anomalies over North Pacific are much weaker. As such, spring AO has weak impacts on the winter ENSO. The spring climatological storm track is stronger during +PDO than −PDO years due to increase in the mean meridional temperature gradient over North Pacific. Stronger storm track intensity during +PDO leads to stronger synoptic-scale eddy feedback to the mean flow, which results in stronger AO-related SST and atmospheric anomalies over the North Pacific and thus the stronger impact of the spring AO on the following winter ENSO.